Early Growth Performances of Three Legumes (Albizia lebbeck, Leucaena leucocephala and Parkia biglobosa) and Their Effects on the Nitrogen Content of Three Soil Types - I. A., Kareem; R. A., Animasaun (Journal of Advance Research in Applied Science (ISSN 2208-2352), 2018)
The fact that numerous benefits are derivable from certain tree legumes especially in the sphere of nitrogen fixation, soil fertility improvement, land reclamation and fodder cannot be over emphasized. Thus, early growth studies on the morphological indices of three leguminous /nitrogen fixing trees (Albizia lebbeck, Leucacea leucocephala and Parkia biglobosa) as influenced by different soil types and variation in their nitrogen fixation potentials were investigated. It was a 3 x 3 factorial experiment in completely randomized design comprising 2 factors (soil types and tree species) each at three levels. Initial / pre-experimental soil analysis, seed sowing/planting in three soil types (river sand, clay, loam) tending operations (watering, thinning, weeding, insect control), data collection on seedling emergence (S.E.), morphological growth parameters (plant height, number of leaves/branches, collar, leaf area) for 12 weeks, post experimental soil analysis and data analysis were carried out. Results indicated that A. lebbeck and P. biglobosa seeds sown in river sand and clayey soil respectively had the fastest germination/ S.E. rate (10 days after planting) and the least were seeds planted in clayey soil. Outstanding performances were observed in L. leucocephala and A. lebbeck seedlings planted in loamy soil while P. biglobosa was the least in most of treatment combinations. Analysis of variance indicated significant differences (at P?0.05) among all the morphological growth characters. There were variations in percentage nitrogen (%N) fixed, soil analysis showed that A. lebbeck seedlings in river sand had the highest value (6.29%N)\ and the least value (1.45%N) was observed in P. biglobosa (difference between initial and final soil analyses).